Стратегічний потенціал автотранспортного підприємства як аспект його економічної безпеки - Попова, В. В. (Eastern-European Journal of Enterprise Technologies, 2009)
In this article the lighted up role of strategic potential as to the aspect of economic security of motor transport enterprises. Economic security of enterprise is protected of it economic interests from internal and external threats